Erect and Prostrate Spurge Biology and Management in Turf - J. Bryan Unruh; Darcy E. P. Telenko; Barry J. Brecke; Ramon Leon (EDIS)
Erect and prostrate spurges are erect or upright annuals with branched stems. Leaves are opposite and not equal. Stems produce “milky sap.” A large number of spurge species occur in Florida. Reproduction occurs via seed. This 2-page fact sheet was written by J. Bryan Unruh, Darcy E. P. Telenko, Barry J. Brecke, and Ramon Leon, and published by the UF Department of Environmental Horticulture, December 2013.